Guide :

# How do you solve this 6/5(5-4g)=-18

## Research, Knowledge and Information :

### 5g+18-7g+4g=8 - solution - Get Easy Solution

Simple and best practice solution for 5g+18-7g+4g=8 equation. Check how easy it is, ... -2g + 4g = 2g 18 + 2g = 8 Solving 18 + 2g = 8 Solving for variable 'g'.

### 6/5(5-4g)=-18 - Get Easy Solution

Simple and best practice solution for 6/5(5-4g)=-18 equation. Check how easy it is, ... SOLVE: Solution for 6/5(5-4g)=-18 equation: 6/5(5-4g)=-18

### 6/5(5-4g)=-18 - OpenStudy

... =-18what's in the numerator on the left?. $6/5(5-4g)=-18$ $5-4g=-18\frac{5}{6}=-15$ $-4g=-20$ \[g=5 ... Learn how to solve problems with step-by-step ...

### Solve Math Problems

... or solving a real-life problem. From finding the average, to converting units, ... What Do You Need Help With? Statistics Calculator; Calculus Calculator;

### How do you solve 6- 5+ n \geq 18? | Socratic

... 6-5+n>=18 Let's put it into words Six minus five plus n is greater than or equal to eighteen. ... How do you solve #y=|x|# and #y=x+2# using ...

### Solving an Equation - Avvanta

Solving an Equation ... X = 6: Because 3 times 6 = 18: X/4 = 5: If you divide my number by 4, you get 5. ... and how you would solve them: Equation

### 5 Ways to Solve for X - wikiHow - How to do anything

How to Solve for X. There are a number of ways to solve for x, ...

### Home | MIT - Solve

If you have a solution to one of these big global challenges, ... Become part of Solve’s global community and enjoy these member benefits: Access to Solve events;

### Solving One-Step Linear Equations - Purplemath

Solving One-Step Linear Equations (page 2 of 4) Sections: One ... Solve x / 5 = –6; Since the x is divided by 5, I'll want to multiply both sides by 5:

### 6^2 ÷ 2(3) + 4 = ? The Correct Answer - YouTube

Apr 28, 2015 · 6^2 ÷ 2(3) + 4 = ? The Correct Answer ... You may also like my video on 6 ... Can You Solve The Viral 1 + 4 = 5 Puzzle?

## Suggested Questions And Answer :

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}

### How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving to the left is negative line moving down is negative Just assign values for x & y then locate it at the x & y axis.                                                                                                                                                            SOLVE Y                                                                                        POINTS X Y 1 0 SOLVE Y 2 SOLVE X 0 3 1 SOLVE Y 4 SOLVE X 1 5 2 SOLVE Y 6 SOLVE X 2 7 -1 8 SOLVE X -1 9 -2 SOLVE Y 10 SOLVE X -2 11 3 SOLVE Y y=-x-4 sample: in point 1 => if  x = 0 y = - (0) - 4 y = - 4 in point 2 => if y = 0 0 = - x - 4 x = - 4 in point 7 => if x=-1 y = -x -4 y =-(-1) -4 y = +1 - 4 y = - 3 at point 8 => if y = -1 -1 = -x -4 x = -4 + 1 x = - 3 - 3 POINTS X Y 1 0 - 4 2 - 4 0 3 1 - 5 4 - 5 1 5 2 - 6 6 - 6 2 7 -1 8 - 3 -1 9 -2 - 2 10 - 2 -2 11 3 - 7 if you have done the 1 to 4 then you can plot the points from 1 to 11 and there is your graph.

### x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4) x + y = 6 Multiply equation 2 by 5. 5(y + z) = 9 * 5 5) 5y + 5z = 45 Subtract equation 3 from equation 5.             5y + 5z = 45 -(-2x + 3y + 5z = 33) --------------------------     2x + 2y        = 12 6) 2x + 2y = 12 Multiply equation 4 by 2. 2(x + y) = 6 * 2 7) 2x + 2y = 12 Subtract equation 7 from equation 6.    2x + 2y = 12 -(2x + 2y = 12) --------------------   0x      = 0      We are solving for x, not y x = 0    <<<<<<<<<<<<<<<<<<< Use equation 4 to solve for y. x + y = 6 0 + y = 6 y = 6    <<<<<<<<<<<<<<<<<<< Use equation 3 to solve for z. -2x + 3y + 5z = 33 -2(0) + 3(6) + 5z = 33 0 + 18 + 5z = 33 5z = 15 z = 3    <<<<<<<<<<<<<<<<<<< Check the values. 1) x - z = -3    0 - 3 = -3    -3 = -3 2) y + z = 9    6 + 3 = 9    9 = 9 3) -2x + 3y + 5z = 33    -2(0) + 3(6) + 5(3) = 33    0 + 18 + 15 = 33    33 = 33 Those numbers work..... ------------- What if we had solved for y instead of x here:    2x + 2y = 12 -(2x + 2y = 12) -------------------        0y = 0      We are solving for y, not x y = 0    <<<<<<<<<<<<<<<<<<< Use equation 4 to solve for x. x + y = 6 x + 0 = 6 x = 6    <<<<<<<<<<<<<<<<<<< Use equation 3 to solve for z. -2x + 3y + 5z = 33 -2(6) + 3(0) + 5z = 33 -12 + 0 + 5z = 33 5z = 45 z = 9    <<<<<<<<<<<<<<<<<<< Check the values. 1) x - z = -3    6 - 9 = -3    -3 = -3 2) y + z = 9    0 + 9 = 9    9 = 9 3) -2x + 3y + 5z = 33    -2(6) + 3(0) + 5(9) = 33    -12 + 0 + 45 = 33    33 = 33 Those numbers work, too. That complicates the solution. Answer 1: x = 0, y = 6, z = 3 Answer 2: x = 6, y = 0, z = 9

### (13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: x + -3x = -2x -3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Reorder the terms: -3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2 Combine like terms: 5 + -5 = 0 -3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2 -3 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 -3 + -2x + x2 = 0 + -1x2 + x2 -3 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 -3 + -2x + x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-1, 3}

### (8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -8 + 8x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + 4x + -1x2) = 0 Factor a trinomial. 2((-2 + x)(2 + -1x)) = 0 Ignore the factor 2. Subproblem 1 Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2 Subproblem 2 Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2 Solution x = {2, 2}

### Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}

### 3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer how do you solve it and what are the answers ? 1)  3x + 6y – 6z = 9 2)  2x – 5y + 4z = 6 3)  -x +16y + 14z = -3 The first objective is to eliminate z so we can solve for x and y. It's a multi-step process, so follow along. Multiply equation one by 4. 4 * (3x + 6y – 6z) = 9 * 4 4)  12x + 24y - 24z = 36 Multiply equation 2 by 6. 6 * (2x – 5y + 4z) = 6 * 6 5)  12x - 30y + 24z = 36 Now, we have two equations with a "24z" term. Add the equations and the z drops out. Add equation five to equation four.    12x + 24y - 24z = 36 +(12x - 30y + 24z = 36) ----------------------------------    24x -  6y           = 72 6)  24x - 6y = 72 The same process applies to equations two and three. Multiply equation two by 7 this time. 7 * (2x – 5y + 4z) = 6 * 7 7)  14x - 35y + 28z = 42 Multiply equation three by 2. 2 * (-x + 16y + 14z) = -3 * 2 8)  -2x + 32y + 28z = -6 Subtract equation eight from equation seven.   14x - 35y + 28z = 42 -(-2x + 32y + 28z = -6) ---------------------------------   16x - 67y          = 48 9)  16x - 67y = 48 Looking at equations six and nine, it would be simpler to eliminate the x. The multipliers are smaller. Multiply equation six by 2. 2 * (24x - 6y) = 72 * 2 10)  48x - 12y = 144 Multiply equation nine by 3. 3 * (16x - 67y) = 48 * 3 11)  48x - 201y = 144 Subtract equation eleven from equation 10.   48x -   12y = 144 -(48x - 201y = 144) ---------------------------          189y  =   0 189y = 0 y = 0  <<<<<<<<<<<<<<<<<<<<<<<<<<<<<< Substitute that value into equations six and nine to solve for x and verify. Six: 24x - 6y = 72 24x - 6(0) = 72 24x - 0 = 72 24x = 72 x = 3  <<<<<<<<<<<<<<<<<<<<<<<<<<<<<< Nine: 16x - 67y = 48 16x - 67(0) = 48 16x - 0 = 48 16x = 48 x = 3    same answer for x To solve for z,substitute the x and y values into the three original equations. One: 3x + 6y – 6z = 9 3(3) + 6(0) – 6z = 9 9 + 0 - 6z = 9 9 - 6z = 9 -6z = 9 - 9 -6z = 0 z = 0  <<<<<<<<<<<<<<<<<<<<<<<<<<<<<< Two: 2x – 5y + 4z = 6 2(3) – 5(0) + 4z = 6 6 - 0 + 4z = 6 6 + 4z = 6 4z = 6 - 6 4z = 0 z = 0     same answer Three: -x +16y + 14z = -3 -(3) +16(0) + 14z = -3 -3 + 0 + 14z = -3 -3 + 14z = -3 14z = -3 + 3 14z = 0 z = 0     once again, same answer x = 3, y = 0, z = 0

### what is general solution for dw/dt = 7w+6y-10z

what is general solution for dw/dt = 7w+6y-10z dx/dt= 3w + x +3y-5z dy/dt= 5w+2x+11y-14z dz/dt=5w+2x+8y-11z Represent the coupled differential equations in matrix form. X = Av Where X is the column vector [w’ x’ y’ z’] and x’ = dx/dt, etc. And A is the component matrix, |7  0   6  -10| |3  1   3    -5| |5  2 11  -14| |5  2   8   -11| And v is the column vector [w x y z] To find the solutions to the original coupled differential equations we need to solve Av = λv for eigenvalues and eigenvectors. i.e. det(A –λI) = 0 or, |7-λ  0     6      -10| = 0 |  3  1-λ   3        -5| |  5    2  11-λ   -14| |  5    2    8    -11-λ| (7-λ){(1-λ)[(11-λ)(-11-λ) – (-14)(8)] – 3[2(-11-λ) – (-14)(2)] + (-5)[2*8 – (11-λ)*2]} – 0 + 6{3[2(-11-λ) – (-14)*2] – (1-λ)[5*(-11-λ) – (-14)*5] + (-5)[5*2 – 2*5]} – (-10){3[2*8 – (11-λ)2] – (1-λ)[5*8 – (11-λ)*5] + 3[5*2 – 2*5]} = 0 You could evaluate and solve the above expression for λ manually, or use an algebra software package such as Maple, Matlab or Mathematica. The solutions for λ are, λ = 1, λ = 1, λ = 3, λ = 3 i.e. four solutions with two roots repeated twice. The eigenvectors are got by solving Av = λv, for λ = 1, 3  i.e. |7  0   6  -10 ||w| = |w|   and   |7  0   6  -10 ||w| = |3w|   |3  1   3    -5 || x|     |x|              |3  1   3    -5 || x|     |3x| |5  2 11  -14|| y|     | y|             |5  2 11  -14|| y|     | 3y| |5  2   8   -11|| z|     | z|             |5  2   8   -11|| z|     | 3z| Giving, 7w + 6y – 10z = w                 and       7w + 6y – 10z = 3w 3w + x + 3y – 5z = x                            3w + x + 3y – 5z = 3x 5w + 2x + 11y – 14z = y                      5w + 2x + 11y – 14z = 3y 5w + 2x + 8y – 11z = z                         5w + 2x + 8y – 11z = 3z   The solution of which is:                    The solution of which is: w = 2, x = 1, y = 3, z = 3                       w = 2, x = 1, y = 2, z = 2 i.e. v1 = [2, 1, 3, 3]                               i.e. v2 = [2, 1, 2, 2] Independent solutions of the coupled equations then are, x1 = v1.e^t,   x3 = v2.e^(3t)   Repeated roots λ = 1, and one solution is x1. A 2nd solution is x2 = t.x1 + p.e^t Where p is solved from (A – λI)p = v1 | 6  0   6   -10||p1| = |2| | 3  0   3     -5||p2|    |1| | 5  2  10 -14||p3|    |3| | 5  2   8  -12||p4|    |3| Giving, p = [p1, p2, p3, p4] = [k, k, k, k] Taking k = 1, p = [1, 1, 1, 1] Then x2 = t.v1.e^t + p.e^t   λ = 3, and one solution is x3. A 2nd solution is x4 = t.x3 + q.e^(3t) Where q is solved from (A – λI)q = v2 | 4   0   6   -10||q1| = |2| | 3  -2   3     -5||q2|    |1| | 5   2   8   -14||q3|    |2| | 5   2   8   -14||q4|    |2| Giving, q = [q1, q2, q3, q4] = [2k, k, 2k+ 2, 2k + 1] Taking k = 0, q = [0, 0, 2, 1] Then x4 = t.v2.e^(3t) + q.e^(3t) Our general solution then is: x = c1.x1 + c2.x2 + c3.x3 + c4.x4 x = c1.v1.e^t + c2{ t.v1.e^t + p.e^t } + c3.v2.e^(3t) + c4{ t.v2.e^(3t) + q.e^(3t) }

### solve for x: 3x^2-5x+2=0

Problem: solve for x: 3x^2-5x+2=0 solve for x: 3x^2-5x+2=0 (3x - 2)(x - 1) = 0    set each factor to zero and solve for x (3x - 2) = 0 3x = 2 x = 2/3 (x - 1) = 0 x = 1 Check. 3x^2 - 5x + 2 = 0 3(2/3)^2 - 5(2/3) + 2 = 0 3(4/9) - 10/3 + 2 = 0 4/3 - 10/3 + 2 = 0 -6/3 + 2 = 0 -2 + 2 = 0 0 = 0 3x^2 - 5x + 2 = 0 3(1)^2 - 5(1) + 2 = 0 3(1) - 5 + 2 = 0 3 - 5 + 2 = 0 0 = 0 x = 2/3   and   x = 1

### solve for x when (.182+x)/(.106-2x)=3.24

solve for x when (.182+x)/(.106-2x)=3.24 Im trying to solve for x its for a chemistry equation but i need to solve for x using the quadratic equation and i dont know which equals a b and c to find x. ************************** You can't solve this with the quadratic formula, because there is no x^2 term. Observe: (.182+x)/(.106-2x)=3.24 Multiply both sides by (.106-2x) to eliminate the fraction on the left. (.106-2x) * (.182+x)/(.106-2x) = (.106-2x) * 3.24 0.182 + x = 0.34344 - 6.48x This is a linear equation. Even if you arranged it so that all the terms are on the left, leaving a zero on the right side, you still would not have an x^2 term. That means that the "a" coefficient would be zero. When you try to use that in the quadratic formula, the denominator would be 2a = 2 * 0 = 0. You cannot divide by zero, so you are now stuck, with no possible solution. If you solve the equation from where I have taken it, you will find the value of x. 0.182 + x = 0.34344 - 6.48x 6.48x + x = 0.34344 - 0.182 7.48x = 0.16144 (Note that you could now subtract 0.16144 from both sides to get 7.48x - 0.16144 = 0, but you still don't have an x^2 term, so a=0, b=7.48 and c=-0.16144. That pesky 0 for the value of a will give that 0 denominator. Impossible to divide.) x = 0.0215828877